A NEW PERMEABILITY PREDICTION WORKFLOW USING 3D POROUS MEDIA RECONSTRUCTION METHOD, CASE STUDIES: MALAY BASIN THIN SECTIONS - Lubis, Luluan Almanna (2012)
Present paper describes a new workflow for predicting laboratory scale permeability from thin section images. The workflow was applied on three thin sections from Malay Basin. In this workflow, instead of using a part image of thin section, full thin section image, which covers whole image of thin section (cm scale), was used as an input to predict permeability at laboratory scale. The workflow is using 3D porous media reconstruction method from 2D image and 3D fluid flow simulation using Lattice Boltzmann Method (LBM) to estimate permeability at pore scale level. To define heterogeneities at laboratory scale on full thin section image, grain size vertical profile was calculated. Building blocks were determined based on grain size vertical profile trends. Upscaling from pore to core plug scale was applied on full thin section image of Malay Basin Sandstone. The estimation of laboratory scale permeability through this workflow correspond well (~85 – 90% accuracy) with available lab measurement data which were measured from core plugs at the same formation where the thin sections were created. With good accuracy and can be applied on standard personal computer in real time (~180 Seconds) this workflow can be used as an alternative and complimentary data to predict permeability when the core plugs are not available.